PENGARUH PADLET TERHADAP TINGKAT KETERAMPILAN MENULIS DAN BERKOLABORASI (PENELITIAN EKSPERIMEN DI KELAS 4 SD HARAPAN KASIH) - Feby Riski Ariyani, - (2022)
Feby Riski Ariyani. 2022. The Effect of Padlet on the Level of Writing and Collaboration Skills (Experimental Research in Grade 4 of Harapan Kasih Elementary School). Elementary School Teacher Education Study Program, Serang Regional Campus, Indonesian University of Education. The use of technology as a medium in the implementation of learning can assist teachers in improving student competencies as well as creating new learning experiences for students. One of the technologies that can be used by teachers as learning media is Padlet. In general, many teachers are not familiar with Padlet. Even though Padlet can be used by teachers in designing language learning, namely writing. Padlet has simple features that are easy to apply. One of the features in Padlet also opens opportunities for students and teachers to collaborate on writing activities in the same room. In this study, Padlet was used to support writing learning while creating a collaborative learning atmosphere in an online classroom setting. This study aims to determine the effect of using Padlet media on the level of writing and collaborating skills in 4th grade students at Harapan Kasih Elementary School. The research method used is an experimental method with a pre-experimental form with a one group pretest-posttest design. The results of this study indicate that there is an average difference in narrative essay writing skills from the original average of 71 to 83 and in collaboration skills from the original average of 53 to 82. In addition, the results of the paired sample t-test also show a significant effect of the use of Padlet media on the value of students' writing and collaboration skills. It can be concluded that the use of Padlet media has a significant effect on the level of writing and collaboration skills. Thus, Padlet can be used as an alternative media to support language learning as well as to create collaborative learning. Keywords: Padlet, writing skills, collaboration skills